Akupresur dalam Menangani Mual dan Muntah pada Ibu Hamil Trimester I di Puskesmas Kecamatan Vera Cruz Timor Leste - Rosalinah; Rachel Nurwidi Annisa; Olimpia M.de Araujo; Palmira de Jesus Gomes; Emilia dos Santos; Luciana Aparicio Soares; Agusriani; Ari Widyaningsih (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2026)
First-trimester pregnancy is often characterized by nausea and vomiting (emesis gravidarum), which can significantly impair the quality of life of pregnant women. Although physiological, this condition can lead to dehydration, decreased appetite, and fatigue if not adequately managed. Acupressure at Pericardium 6 (P6/Nei Guan) point has been recognized as a safe and effective non-pharmacological intervention to alleviate these symptoms. This study aimed to evaluate the improvement in knowledge, understanding, and skills of first-trimester pregnant women at the Vera Cruz Community Health Center, Timor Leste, in managing nausea and vomiting through acupressure therapy. This community service method involved 20 first-trimester pregnant women experiencing nausea and vomiting, with interventions including education, demonstration, and direct practice of P6 acupressure. Data were collected using pretest-posttest questionnaires for knowledge and observation sheets for skills. The results showed a significant increase in the knowledge and skills levels of pregnant women after the intervention. The in-depth discussion elaborates on the mechanism of P6 acupressure, compares the findings with current scientific literature, and highlights the practical implications of applying acupressure in primary healthcare services. This study affirms the potential of acupressure as an accessible, safe, and effective modality for managing nausea and vomiting, as well as the importance of health education for empowering pregnant women.   Abstrak Kehamilan trimester pertama seringkali diwarnai dengan keluhan mual dan muntah (emesis gravidarum) yang dapat mengganggu kualitas hidup ibu hamil. Kondisi ini, meskipun fisiologis, berpotensi menyebabkan dehidrasi, penurunan nafsu makan, dan kelelahan jika tidak ditangani secara adekuat. Akupresur pada titik Pericardium 6 (P6/Nei Guan) telah dikenal sebagai intervensi nonfarmakologis yang aman dan efektif untuk meredakan gejala ini. Penelitian ini bertujuan untuk mengevaluasi peningkatan pengetahuan, pemahaman, dan keterampilan ibu hamil trimester I di Puskesmas Kecamatan Vera Cruz, Timor Leste, dalam mengelola mual dan muntah melalui terapi akupresur. Metode pengabdian masyarakat ini melibatkan 20 ibu hamil trimester I yang mengalami mual dan muntah, dengan intervensi berupa penyuluhan, demonstrasi, dan praktik langsung akupresur P6. Data dikumpulkan melalui kuesioner pretest-posttest untuk pengetahuan dan lembar observasi untuk keterampilan. Hasil menunjukkan peningkatan signifikan pada tingkat pengetahuan dan keterampilan ibu hamil setelah intervensi. Pembahasan mendalam menguraikan mekanisme akupresur P6, membandingkan temuan dengan literatur ilmiah terkini, serta menyoroti implikasi praktis dari penerapan akupresur dalam pelayanan kesehatan primer. Studi ini menegaskan potensi akupresur sebagai modalitas penanganan mual dan muntah yang mudah diakses, aman, dan efektif, serta pentingnya edukasi kesehatan untuk pemberdayaan ibu hamil.